Production of Biologically Activated Carbon from Orange Peel and Landfill Leachate Subsequent Treatment Technology - Zhigang Xie; Wei Guan; Fangying Ji; Zhongrong Song; Yanling Zhao (Journal of Chemistry)
In order to improve adsorption of macromolecular contaminants and promote the growth of microorganisms, active carbon for biological wastewater treatment or follow-up processing requires abundant mesopore and good biophile ability. In this experiment, biophile mesopore active carbon is produced in one-step activation with orange peel as raw material, and zinc chloride as activator, and the adsorption characteristics of orange peel active carbon is studied by static adsorption method. BET specific surface area and pore volume reached 1477 m2/g and 2.090 m3/g, respectively. The surface functional groups were examined by Fourier transform infrared spectroscopy (FT-IR). The surface of the as-prepared activated carbon contained hydroxyl group, carbonyl group, and methoxy group. The analysis based on X-ray diffraction spectrogram (XRD) and three-dimensional fluorescence spectrum indicated that the as-prepared activated carbon, with smaller microcrystalline diameter and microcrystalline thickness and enhanced reactivity, exhibited enhanced adsorption performance. This research has a deep influence in effectively controlling water pollution, improving area water quality, easing orange peel waste pollution, and promoting coordinated development among society, economy, and environment.